2016
DOI: 10.3892/mmr.2016.6065
|View full text |Cite
|
Sign up to set email alerts
|

Tim-3 is upregulated in human colorectal carcinoma and associated with tumor progression

Abstract: T cell immunoglobulin mucin-3 (Tim-3) has previously been implicated in the immune response and tumor biology. Colorectal carcinoma (CRC) is a malignancy, which is closely associated with inflammation. However, the role of Tim-3 in the progression of CRC remains to be fully elucidated. The present study aimed to investigate the role of Tim-3 in the progressive activities of human CRC. A total of 30 clinical CRC tissues and their adjacent tissues were collected. Slides from another 112 cases that underwent CRC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
37
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 27 publications
(30 reference statements)
7
37
2
1
Order By: Relevance
“…Knockdown of TIM-3 in CRC cell lines HCT116 and HT-29 significantly reduced cell proliferation rates compared with controls [9]. TIM-3 also promotes inflammation through the synergetic action with TLR signaling in immune cells [9]. Our network analysis showed that immune cell trafficking/inflammatory response-mediated genes were upregulated in TIM-3 + T cells (Figure 3 and Figure S4A).…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…Knockdown of TIM-3 in CRC cell lines HCT116 and HT-29 significantly reduced cell proliferation rates compared with controls [9]. TIM-3 also promotes inflammation through the synergetic action with TLR signaling in immune cells [9]. Our network analysis showed that immune cell trafficking/inflammatory response-mediated genes were upregulated in TIM-3 + T cells (Figure 3 and Figure S4A).…”
Section: Discussionmentioning
confidence: 87%
“…The expression of TIM-3 at higher levels in colorectal cancer tissues is significantly associated with tumor size and tumor-node/distant metastasis [9]. Knockdown of TIM-3 in CRC cell lines HCT116 and HT-29 significantly reduced cell proliferation rates compared with controls [9]. TIM-3 also promotes inflammation through the synergetic action with TLR signaling in immune cells [9].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations